2015
DOI: 10.1242/dev.114769
|View full text |Cite
|
Sign up to set email alerts
|

Nesprins anchor kinesin-1 motors to the nucleus to drive nuclear distribution in muscle cells

Abstract: During skeletal muscle development, nuclei move dynamically through myotubes in a microtubule-dependent manner, driven by the microtubule motor protein kinesin-1. Loss of kinesin-1 leads to improperly positioned nuclei in culture and in vivo. Two models have been proposed to explain how kinesin-1 functions to move nuclei in myotubes. In the cargo model, kinesin-1 acts directly from the surface of the nucleus, whereas in an alternative model, kinesin-1 moves nuclei indirectly by sliding anti-parallel microtubul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
110
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(115 citation statements)
references
References 54 publications
5
110
0
Order By: Relevance
“…A kinesin-1– nesprin-2 interaction contributes to nuclear spacing in syncytial myotubes [16], but forward nuclear recentering primarily occurred toward MT minus ends and depended on dynein (Figure 3). Dynein and nesprin-2 contribute to centrosomal-directed nuclear movement in migrating neurons, and dynein has been reported to associate with nesprin-2 [13, 41].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A kinesin-1– nesprin-2 interaction contributes to nuclear spacing in syncytial myotubes [16], but forward nuclear recentering primarily occurred toward MT minus ends and depended on dynein (Figure 3). Dynein and nesprin-2 contribute to centrosomal-directed nuclear movement in migrating neurons, and dynein has been reported to associate with nesprin-2 [13, 41].…”
Section: Resultsmentioning
confidence: 99%
“…For example, in C. elegans ANC-1 interacts with actin filaments through paired calponin homology (CH) domains [8], whereas UNC-83 engages MTs through kinesin-1 and cytoplasmic dynein motor proteins [9]. In mammalian cells, nesprin-1G and nesprin-2G (“G” refers to the giant isoform) have paired CH domains that interact with actin filaments [10-12], but also engage MTs through MT motors [13-16]. Nesprin-2G's interaction with actin filaments is reinforced by its interaction with two other actin binding proteins, FHOD1 and fascin [17, 18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The additional model is the cargo model. The Holzbaur lab showed that Nesprin-1 and Nesprin-2 recruit kinesin-1 to cargo, the nucleus, through their LEWD motifs that binds directly to kinesin light chains [19]. This model is distinct from the microtubule-nucleation model because mutating the LEWD motif in Nesprin-1α did not disrupt the microtubule-nucleation activity of Nesprin-1α [7].…”
mentioning
confidence: 99%
“…Together, these results suggest LINC complexes are primarily involved in centrosome-mediated nuclear translocations, where mechanical forces are exerted by kinesin-1 and dynein whose direct interactions with KASH proteins are conserved in evolution [28,4447]. Actin networks may also contribute to this force, since an actin-dependent pathway acts in parallel with SUN/KASH interactions to move nuclei in C. elegans [48].…”
Section: Nuclear Translocation Within Post-mitotic Neurons: Major Rolmentioning
confidence: 99%